The effect of project based learning (PJBL) on student economics and business mathematics learning outcomes: analysis on the topic of taxes and subsidies - Hastuti, Dwi; Hardiani, Hardiani (Jurnal Paradigma Ekonomika, 2024)
This research aims to investigate the influence of the integrated Project Based Learning (PBL) Model of Science, Technology, Engineering, and Mathematics (STEM) on students' learning outcomes in economic and business mathematics, specifically on the concept of tax and subsidy analysis in the Development Economics Study Program, Faculty of Economics and Business. Economics and business mathematics courses are crucial in developing student competencies in understanding basic concepts and applications, including taxes and subsidies. The research method used is an experimental design with a control group. Eight groups of students studying tax and subsidy material were chosen to receive experimental questions. The method used is classroom action research. The aspects of students' scientific work skills observed included skills in asking questions, planning experiments, making observations, using tools/materials, analyzing experimental results, drawing conclusions, compiling experimental reports, and presentation skills. Analysis of critical thinking skills is around 50% and analysis of student enthusiasm level is around 82 which is quite high in cycle II. In addition to scientific work skills, students' conceptual knowledge and relative creativity also increased by 62.5%. The conclusion of this research is that the application of the STEM-integrated Project Based Learning model with tax and material subsidies can improve students' scientific skills. This integrated model can be used as an alternative learning approach to enhance students' scientific skills in mathematics, economics, and business courses.